The Longitudinal Interplay Between Social Network and Psychopathology in Multi-Problem Young Adult Men; Separating Within-and Between-Person Effects - Schenk, Loïs; Sentse, Miranda; Marhe, Reshmi; van Duin, Laura; Engbersen, Godfried; Popma, Arne; Severiens, Sabine (Frontiers in Psychology, 2021)
Young adulthood is characterized by many life changes. Especially for young men with problems across different life domains (i.e., multi-problem), these changes may entail obstacles. Incidences of psychopathology increase during young adulthood and at the same time important shifts in social networks – such as changing relations with peers and parents, isolation, or deviant peer affiliation – take place. The present study examined the longitudinal interplay between psychopathology and social network characteristics over the course of one year in multi-problem young adults, at both between-person and within-person level. A sample of 696 multi-problem young adult men (age 18-27) participated in this three wave study. We used traditional cross-lagged panel models (CLPM) to examine how social network characteristics and psychopathology are related at the between-person level, and random intercept cross-lagged panel models (RI-CLPM) to examine within-person links. Between-person associations between internalizing problems and social networks were bidirectional, and externalizing problems were related to problematic social network characteristics, but not vice versa. At the within-person level, no such cross-lagged paths were found. Overall, results indicated that in multi-problem young adults, social network characteristics and psychopathology are related. However, looking at within-person processes this relation is not reciprocal.